2020
DOI: 10.1097/cnq.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Institutional COVID-19 Protocols

Abstract: As the confirmed cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continue to grow with over 1 million documented infections in the United States alone, researchers and health care workers race to find effective treatment options for this potentially fatal disease. Mortality remains high in patients whose disease course requires mechanical ventilation and admission to intensive care units. While focusing on therapies to decrease mortality is essential, we must also consider the logistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These shortages led many organizations to ration existing PPE, re‐sterilize masks, or to devise makeshift PPE out of non‐traditional items ranging from scuba masks to plastic garbage bags 13–16 . Many institutions modified the guidelines instated by WHO and CDC to optimize safety and use of limited protective resources in their specific populations of health care workers in settings such as operating rooms (ORs), ICUs, or primary care units 17–19 . Such institution‐specific measures were needed in the absence of the ability to order standard supplies in a timely manner, as reported fear of contracting COVID‐19 among health care workers escalated 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These shortages led many organizations to ration existing PPE, re‐sterilize masks, or to devise makeshift PPE out of non‐traditional items ranging from scuba masks to plastic garbage bags 13–16 . Many institutions modified the guidelines instated by WHO and CDC to optimize safety and use of limited protective resources in their specific populations of health care workers in settings such as operating rooms (ORs), ICUs, or primary care units 17–19 . Such institution‐specific measures were needed in the absence of the ability to order standard supplies in a timely manner, as reported fear of contracting COVID‐19 among health care workers escalated 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Many institutions modified the guidelines instated by WHO and CDC to optimize safety and use of limited protective resources in their specific populations of health care workers in settings such as operating rooms (ORs), ICUs, or primary care units. [17][18][19] Such institution-specific measures were needed in the absence of the ability to order standard supplies in a timely manner, as reported fear of contracting COVID-19 among health care workers escalated. 20,21 Health care workers have indicated that they feel more comfortable using PPE if they receive consistent communication and training regarding their correct use from their institution.…”
Section: Introductionmentioning
confidence: 99%